1996
DOI: 10.1177/030802269605900104
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Therapy: A Critical Overview, Part 2

Abstract: Rrt 2 of this article continues the evaluation of philosophical concepts that began In part 1. It concludes by suggesting that the foundation of the profession does not rest on the dictum 'health through occupation' but on the field related to the learning and teaching of skills, and stresses the importance and potential that this field has for the future viability of occupational therapy. In this context, the need for recognising the distinction that exists between the Inherent competence of Individuals, as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…Mocellin (96) claimed that the occupational therapy profession failed to subject its core assumptions to critical scrutiny because those in positions of power had invested heavily in the profession's conventional rhetoric. He also observed that "when core assumptions, which are considered essential to the underpinning of occupational therapy, are perceived by some to be under threat, considerable efforts are made to enforce professional conformity" [(12), p. 502].…”
Section: Resultsmentioning
confidence: 99%
“…Mocellin (96) claimed that the occupational therapy profession failed to subject its core assumptions to critical scrutiny because those in positions of power had invested heavily in the profession's conventional rhetoric. He also observed that "when core assumptions, which are considered essential to the underpinning of occupational therapy, are perceived by some to be under threat, considerable efforts are made to enforce professional conformity" [(12), p. 502].…”
Section: Resultsmentioning
confidence: 99%
“…Critics observe that the more powerful one's beliefs and assumptions become and the greater their longevity, the greater their ability to survive contact with contesting evidence (Childs & Williams, 1997;Taylor, 1999). Moreover, Mocellin (1996) claimed that instead of subjecting its core assumptions to critical scrutiny, occupational therapy has promoted specific language and models, not solely to advance the scientific basis of the profession, but as a defensive response by those who have invested heavily in the profession's conventional rhetoric. Mocellin (1995) therefore equates these beliefs and assumptions with the dogma of a fundamentalist faith.…”
Section: Assumptions and Theory In Occupational Therapymentioning
confidence: 99%
“…(This is not a view subscribed to by all; see Mocellin [1995Mocellin [ , 1996 for a review of this topic.) Pasquinelli (1996) continued by stating:…”
Section: They Later Claimedmentioning
confidence: 99%